Associations between exposure to organophosphate esters and overactive bladder in U.S. adults: a cross-sectional study - Lin, Weilong; Wang, Haoxu; Wu, Zesong; Zhang, Wei; Lin, Ming-En (Frontiers in Public Health, 2023)
Abstract Background The relationship between exposure to organophosphate esters (OPEs) and the risk of developing overactive bladder (OAB) is uncertain. The purpose of this study is to examine the potential link between urinary metabolites of organophosphate esters and OAB. Method Data from the National Health and Nutrition Examination Survey (NHANES) database of the 2011–2016 cycles were utilized. Four urinary metabolites of organophosphate esters: diphenyl phosphate (DPHP), bis (1,3-dichloro-2-propyl) phosphate (BDCPP), bis (2-chloroethyl) phosphate (BCEP), and dibutyl phosphate (DBUP) were included in the study. Multivariate logistic regression and restricted cubic spline (RCS) were used to evaluate the relationship between urinary OPEs metabolites and OAB. Interaction analysis was conducted on subgroups to confirm the findings. Results A total of 3443 United States (US) adults aged 20 years or older were included in the study, of whom 597 participants were considered to have OAB. After adjusting for potential confounding factors, we found a positive association between DPHP and the risk of overactive bladder. The incidence of overactive bladder increased with increasing DPHP concentrations compared with quartile 1 (quartile 2, OR = 1.19, 95% CI, 0.82 - 1.73, P = 0.34; quartile 3, OR = 1.67, 95% CI, 1.10–2.53, P = 0.02; Q4, OR = 1.75, 95% CI, 1.26 - 2.43, P = 0.002). However, after dividing the participants by gender, only the female group retained consistent results. Additionally, restricted cubic spline analysis revealed a nonlinear dose-response correlation between DPHP and OAB in female participants. In the subgroup analysis based on age, race, body mass index (BMI), recreational activity, smoking status, drinking status, hypertension, diabetes, and stroke, the interaction analysis revealed that the findings were uniform. Conclusion Our findings indicate that exposure to DPHP could elevate the risk of OAB in US adult females. Further experimental studies are needed to explore the underlying mechanism in the future.